The Typology of Directive Expressions in Lesia Ukrainka’s Epistolary Texts (Linguostylistic Studies, 2016)
The paper studies the main pragmatic and semantic types of directive expressions in epistolary texts of Lesia Ukrainka, in particular the author singles out expressions with semantic meaning of request, non-categorical request, advice, prohibition and desire. The paper systematizes grammatical means of expressing inductive modality, which form the core and peripheral zones of the analyzed corpus. The most frequent are the expressions, which have imperative forms of the second person singular and plural. The peripheral directive expressions encompass grammatical units with etiquette formulae and syntax- dependent infinitive, as well as transferred language units. The paper takes into account a range of extra lingual factors, which influence and determine the success of epistolary communication, and stimulates the detailed analysis of lingual parameters of logic-semantic structures in the situations of inducement in correspondence of Lesia Ukrainka. Analysis of semantic, syntactic and pragmatic aspects of the directive statements in Lesia Ukrainka’s epistolary allows to draw some conclusions as to their categorical specificity. Key words: directive, epistolary, speech causation, inductive modality, typology. References